Wage Hysteresis and Entitlement Effects: The Persistent Impacts of a Temporary Overtime Policy - Simon Quach (The Quarterly Journal of Economics, 2025)
Abstract This article studies the unexpected retraction of a U.S. federal policy in 2016 that would have more than doubled the “overtime exemption threshold” from $455 to $913 per week and thereby grant overtime protection to an additional 20% of salaried workers. Although the policy was blocked by a federal court injunction a week before it was supposed to take effect, I show that it nevertheless had a persistent positive impact on workers’ earnings. Leveraging a bunching design with administrative payroll data from ADP, I find that employers raised workers’ salaries to the $913 threshold even after the policy was repealed. Over the next 18 months, difference-in-difference estimates reveal that employers did not slow the wage growth of workers affected by the policy relative to those already earning above $913 per week, nor did they hire new employees at a lower pay rate. Real wages remained persistently elevated relative to what they would have been absent the policy and separation rates decreased among workers bunched at the $913 threshold. Comparing highly exposed firms to unaffected firms, I find an increase in employers’ wage bills but no change in aggregate employment. Taken together, the results indicate that temporary policies impacting wage levels can have permanent effects on the labor market. Survey responses collected by the Department of Labor suggest that morale concerns play a key role in driving the wage hysteresis.